Analisa Rambatan Salinitas di Sungai Jenu, Batu Ampar, Kalimantan Barat - Catherine, Liany Ayu; Simatupang, Johnny Maruli Tua; Ira, Nurmaya Putri (Universitas Tanjungpura, 2025)
Seawater intrusion is a major threat to freshwater availability in coastal areas, particularly during dry seasons and spring tides. This study aims to analyze the distribution pattern of salinity and determine the maximum distance of seawater intrusion in the Jenu River, Kubu Raya Regency, West Kalimantan, to support the planning of raw water intake locations for the regional water utility (PDAM). Field data were collected over two days during the full moon phase (highest tidal range) at eight observation points along the Jenu Besar and Jenu Kecil Rivers. Salinity was measured at three vertical depths (0.2d, 0.6d, and 0.8d). The results show that the highest salinity values were observed near the river mouth at the bottom layer, while the lowest concentrations were found upstream at the surface layer. Polynomial regression analysis revealed a strong correlation between distance from the estuary and salinity concentration, with determination coefficients (R ²) of 0.9092 for Jenu Kecil and 0.9774 for Jenu Besar. The maximum intrusion distance was estimated to be ±17 km and ±17.5 km, respectively. The resulting polynomial equations can be used to predict salinity zones based on horizontal distance. The study recommends that PDAM raw water intake points be located beyond the intrusion zones (>18 km from the river mouth) to ensure compliance with water quality standards. Identified limitations include the short observation period and absence of real-time discharge and seasonal variation data. Further research is suggested to include hydrodynamic modeling and spatial salinity mapping to enhance the robustness of the findings.